ANALYSIS OF THE DIFFICULTY OF LEARNING MATHEMATICS IN COMPLETING THE OPERATION TO ADD FRACTIONS AT SDN 4 SYAMTALIRA ARON - Samsul Bahri; Muri Datul Jinan; Asmaul Husna Diniati; Mura Datil Jinan; Qathrun Nada Fitria (Prodi Tadris Matematika Universitas Muhammadiyah Aceh, 2024)
The aim of this research is to describe the difficulties of learning mathematics in the material on fractional addition calculation operations in class V of SDN 4 Syamtalira Aron. This data analysis uses descriptive research with a qualitative approach. This research method is qualitative research with the type of research case study being students and teachers of Class V Elementary School. Data collection on mathematics learning difficulties used direct observation and interview techniques. The results of this research show that most students experience learning difficulties in solving mathematical problems on the addition of fractions, the factors of students' difficulties in completing the operation of calculating the addition of fractions and educators' teaching solutions must be improved to overcome learning difficulties by using methods, strategies and media or tools. more varied displaysThe aim of this research is to describe the difficulties of learning mathematics in the material on fractional addition calculation operations in class V of SDN 4 Syamtalira Aron. This data analysis uses descriptive research with a qualitative approach. This research method is qualitative research with the type of research case study being students and teachers of Class V Elementary School. Data collection on mathematics learning difficulties used direct observation and interview techniques. The results of this research show that most students experience learning difficulties in solving mathematical problems on the addition of fractions, the factors of students' difficulties in completing the operation of calculating the addition of fractions and educators' teaching solutions must be improved to overcome learning difficulties by using methods, strategies and media or tools. more varied displays